Transformation of Digital Marketing in the 4.0 Industry Revolution: A Study on Batik MSMEs - Adjeng Mariana Febrianti, R.; Haizam Mohd Saudi, Mohd; Kaniawati, Keni; Hermina, Nurul (International Journal of Engineering and Technology, 2018)
The success of the business cannot be separated from an implementation and utilization of information technology encouraging the creation of a competitive business which can be seen from the effectiveness of its supporting system. Currently, many business owners are inspired to improve their business with digitalization. The 4.0 industry revolution does not only occur in the government environment but also transpires other businesses with traditional culture background. A unique custom contributes advantages to Yogyakarta Special Region (Daerah Istimewa Yogyakarta) which produces traditional hand-drawn batik. The batik pieces are then processed into kemben. This study aims to find out the role of customer satisfaction in order to improve competitiveness through product quality, service quality, and price. This study used a snowball sampling method of 200 respondents analyzed using SEM (Structural Equation Modeling). The result showed that product quality and price affect customer satisfaction through service quality. Eventually, the increasing product quality will provide benefits for Micro Small Medium Enterprises (MSMEs) of kemben in Yogyakarta Special Region and bring improvement for the local economy.Â Â